Teachers' Perspective Toward the Classroom Management of English Teaching-Learning Process in Big Class - Muzlifatul Ulfah; Fitriana Astari Dewi; Dwi Wahyu Yulianti (Journal of Teaching dan Learning Research, 2020)
Education takes effect in human life. Education must depend on empowering all sector of society. Now, in industrial revolution 4.0, education is important to create the students' innovative. So, the school of Indonesia compete to get many new students to fill the amount of the students that were targeted by the Indonesia government. Based on the phenomenon, the purpose of this research was to identify the teacher perspective toward classroom management in the big class. This research was conducted at SMK Muhammadiyah 1 Bantul. This research used a descriptive qualitative approach, and the major instruments used were interview and observation. There were two English teachers that were being involved as a participant in this research. Based on the result of the study, there were three difficulties faced by the English teacher in managing large classes. They are grouping the students, using English in large classes, and making students active. The strategies used by the English teacher in managing large classes are: Arranging the students' seat position, grouping the students, using the media, controlling the students, using humour, interacting, managing the time.